Contributions of a training memorial: formative knowledge about Professional Education integrated to EJA - Kaline Valeria Pereira Silva (Universidade Estadual de Alagoas, 2020)
In view of the call for comprehensive education in the professional training of young people and adults -PROEJA, there is a movement of attention to teacher training and the necessary knowledge to act in this type of teaching. As a result of studies carried out while participating in the Specialization Course in Assertive Practices in Didactics and Management of Professional Education Integrated with Youth and Adult Education -EJA / PROEJA, offered at the Federal Institute of Education, Science and Technology of Rio Grande do Norte -IFRN , this work aims to socialize training knowledge that contributes to the professional development of teachers, starting from a rescue of the significant learnings experienced in the Course on screen. For that, I use the writing of a training memorial as a methodological procedure, reflecting on those knowledgesidentified as characterizing the training proposal. I perceive in the experiences lived the pertinence of investments in training proposals aimed atthe pedagogical updating of the EJA / PROEJA teacher in current approaches on the use of digital information and communication technologies in pedagogical mediation.